The Aapiesboomen magnesite deposit, Burgersfort, Transvaal - Taylor, N C (Rhodes University, Faculty of Science, Department of Geology, 1974)
The published literature on magnesite is extensively reviewed as regards the properties, uses, production, occurrence and genesis of the mineral. Despite opposition from the producers of sea water magnesia in recent years, magnesite still finds a ready market for the manufacture of refractory materials, particularly in the steel industry. Less important uses include the manufacture of magnesium metal, carbonic acid gas, Sorel cement, paper, pharmaceuticals and fertilizers. Large bodies of cryptocrystalline magnesite occur in Greece, Yugoslavia, Turkey and India, while the deposits in Austria, Czechoslovakia, Russia and China produce most of the world supply of crystalline material. Four types of magnesite bodies may be distinguished: quartz-magnesite deposits, talc-magnesite occurrences, magnesite associated with sedimentary rocks and sagvandite, a magnesite-bronzite rock. Most South African deposits, including the Aapiesboomen body, belong to the first type. Experimental, field and textural evidence indicates that the quartz-magnesite deposits may form from serpentine under a wide range of hydrothermal and supergene conditions below about 400Â°C and between very low and very high concentrations of co2 in the fluid phase. Above 400Â°C talc is produced at the expense of quartz. Sedimentary magnesite has been observed t o form in present day saline lakes, but the large size of the older crystalline deposits associated with limestones and dolomites has been used as an argument against the use of the same principle to explain the genesis of the latter bodies : much controversy still surrounds the sedimentary-hydrothermal debate concerning their origin. It seems probable thet sagvandites are produced by a process of CO2- metasomatism.
Keywords: Uncatalogued